Analysis of the codon 72 polymorphism of p53 gene in patients with multinodular goitre: A risk factor of thyroid cancer - Bayram, B.; Sönmez, R.; Bozari, S.; Önlü, H.; Sahin F.M. (Society of Pharmaceutical Sciences of Ankara (FABAD), 2011)
Aim: In this study, it was aimed to determine whether the p53 gene codon 72 polymorphism is a genetic marker of thyroid cancer development in multinodular goitre patients. Methods: Genomic DNA was isolated from 90 persons (42 with multinodular goitre and 48 healthy controls) in the study. DNA was amplified with specific primers by PCR and RFLP technique was used to analyze p53 gene codon 72 polymorphism alleles and genotypes. PCR-RFLP products were assessed with UV transilluminator after application of agarose gel electrophoresis. Results: According to genotype distribution and allele frequencies of p53 gene codon 72 polymorphism, there was no significant difference between groups. Conclusions: As a result of our study we may assert that p53 gene codon 72 polymorphism should not be considered as a genetic marker to develop thyroid cancer in the studied Turkish population with multinodular goitre.
Keywords: Multinodular goitre; P53 gene 72 polymorphism; Thyroid cancer